Chamber executive director Bob Walton resigns (Raton Range Raton, New Mexico, 1978)
Newspaper article on Bob Walton resigning as the Chamber of Commerce Executive Director.
Master list item #: 14
File location is in the Raton file Cabinet
Keywords: Walton, Robert G; Monroe, Aleene; DiMarzio, Rick; Sofranko, Paul; Volpato, Kenn; Tadus, Rick; Smith, Truman; Sims, Jesse; Chamber of Commerce; Luna Vo-Tech School; New Mexico State University; Air Force; Biography; Life and Customs; Local History; Resignation; Insurance agency; Raton, New Mexico